Effects of household access to water, sanitation, and hygiene services on under-five mortality in Sub-Saharan Africa - Gaffan, Nicolas; Kpozehouen, Alphonse; Degbey, Cyriaque; Ahanhanzo, Yolaine Glele; Paraïso, Moussiliou Noël (Frontiers in Public Health, 2023)
Introduction: Sub-Saharan Africa has the highest under-five mortality rate and is among the regions where people have the least access to adequate Water, Sanitation, and Hygiene (WASH) services. The work aimed to investigate the effects of WASH conditions faced by children on under-five mortality in Sub-Saharan Africa. Methods: We carried out secondary analyses using the Demographic and Health Survey databases of 30 countries in Sub-Saharan Africa. The study population consisted of children born within five years preceding the selected surveys. The dependent variable was the child’s status (1 = deceased versus 0 = alive) on the survey day. The individual WASH conditions in which children live were assessed in their immediate environment, i.e. at the level of their households of residence. The other explanatory variables were related to the child, mother, household, and environment. Following a description of the study variables, we identified the predictors of under-five mortality using a mixed logistic regression. Results: The analyses involved 303,985 children. Overall, 6.36% (95% CI = 6.24-6.49) of children died before their fifth birthday. The percentage of children living in households with access to individual basic WASH services was 58.15% (95% CI = 57.51-58.78), 28.18% (95% CI = 27.74-28.63), and 17.06% (95% CI = 16.71-17.41), respectively. Children living in households using unimproved water facilities (aOR = 1.10; 95% CI = 1.04-1.16) or surface water (aOR = 1.11; 95% CI = 1.03-1.20) were more likely to die before five than those coming from households with basic water facilities. The risk of under-five mortality was 11% higher for children living in households with limited sanitation facilities (aOR = 1.11; 95% CI = 1.04-1.18) than for those with basic sanitation services. We found no evidence to support a relationship between household access to hygiene services and under-five mortality. Conclusion: Interventions to reduce under-five mortality should focus on strengthening access to basic water and sanitation services. Further studies are needed to investigate the contribution of access to basic hygiene services on under-five mortality.